2023
DOI: 10.3389/fonc.2023.1120783
|View full text |Cite
|
Sign up to set email alerts
|

Access to advanced cancer care services in the West Bank-occupied Palestinian territory

Abstract: IntroductionUniversal Health Coverage (UHC) identifies the provision of palliative care for people with advanced disease as an essential health service. Palliative care is also stipulated as a human right under existing covenants. Oncology services provided by the Palestinian Authority under Israeli military occupation are limited to surgery and chemotherapy treatment. Our study aimed to describe the experiences of patients with advanced-stage cancer in the West Bank in accessing oncology services and meeting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…Barriers to cancer care and psychosocial support services, physical and financial hardship endured by cancer patients in our study and other studies from similar contexts [ 7 , 19 22 ] are concerning. Cancer treatment requires a multimodal approach, starting with timely diagnosis and person-centred treatment, yet our study and previous studies report many obstacles faced by cancer patients along the continuum of cancer care pathways.…”
Section: Discussionmentioning
confidence: 43%
See 3 more Smart Citations
“…Barriers to cancer care and psychosocial support services, physical and financial hardship endured by cancer patients in our study and other studies from similar contexts [ 7 , 19 22 ] are concerning. Cancer treatment requires a multimodal approach, starting with timely diagnosis and person-centred treatment, yet our study and previous studies report many obstacles faced by cancer patients along the continuum of cancer care pathways.…”
Section: Discussionmentioning
confidence: 43%
“…Cancer treatment requires a multimodal approach, starting with timely diagnosis and person-centred treatment, yet our study and previous studies report many obstacles faced by cancer patients along the continuum of cancer care pathways. This is a recurring problem in conflict-affected contexts, where healthcare infrastructure and supply chains are often compromised [ 4 , 6 , 7 , 19 23 ]. For instance, a recent study found that Palestinian patients with advanced-stage cancer in the West Bank experienced referral delays in accessing treatment as well as going through unpredictable, lengthy processes of obtaining Israeli permits to access cancer care in East Jerusalem [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adherence to the recommended guidelines for diagnosing patients with multiple myeloma was 98%. In Palestine, caring for cancer patients has long been described as fragmented [ 52 , 53 ]. Lack of coordination between hematologists-oncologists, radiologists, pathologists, and surgeons was previously reported [ 52 ].…”
Section: Discussionmentioning
confidence: 99%